Chemistry and Biology of the Clinically Used Macrolactone Antibiotic Fidaxomicin. Issue 4 (9th April 2020) - Dorst, Andrea; Gademann, Karl
Abstract: Fidaxomicin (1, lipiarmycin A3, clostomicin B1, tiacumicin B) constitutes a glycosylated 18‐membered macrolactone and is a natural product isolated from various soil bacteria. Since 2011, fidaxomicin is a marketed antibiotic for the treatment of intestine infections caused by C. difficile in the clinic. Its promising in vitro antibacterial properties against resistant S. aureus and M. tuberculosis continue to attract interest. This review article describes the early history of the antibiotic fidaxomicin and highlights recent advances in the field, such as the elucidation of its mode of action and biosynthesis, as well as known derivatives. Furthermore, different synthetic strategies towards the total synthesis of fidaxomicin are summarized. Abstract :